Female Student Prevention on Health Awareness at Padjadjaran Vocational High School - Rifiza, Muhammad Irfa; Dermawan, Windy; Nurhayati, Heni (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2024)
Healthy generation is one of the keys to achive "Indonesia Emas 2045" envisioned by The Ministry of National Development Planning of Indonesia. To realize the vision, Indonesia should ensure the health of its citizens. Adolescents should become the priority because their nutrition and health might determine the quality of their future which implies the future of Indonesia's human resources quality. Anemia is a serious problem faced by Indonesia which has a prevalence of more than 40%. This paper aims to illuminate the anemia prevention efforts of female students at Padjadjaran Vocational High School. The design used in this study is qualitative, using a case study approach. The subjects of the study are Puskesmas Jatinangor, the program coordinator, and female students. Data were collected through observation, interviews, and documentation. The data validity technique used in this study is source and technique triangulation, with data analysis using organize the data which involve transcribing interview from the informants, peruse the data by finding general ideas from the informants, code the data using Atlas.ti software to write words representing category, generate a description of the setting or people as well as categories or themes for analysis, determine the ideas and description will be conveyed in the qualitative narrative, interpreting the data and explain the female student prevention at Padjadjaran Vocational High School Jatinangor. The results showed that Padjadjaran Vocational High School, collaborating with Puskesmas, holds an anemia prevention program in that includes anemia prevention dissemination to students in Padjadjaran Vocational High School conducted every three months, monthly blood check up to ensure students are not potentially suffered from anemia and prevent students from further disease, and providing blood supplement tablets to female students every week.